Siege of Caudebec in 1592 (engraving) - J. Gerlier (Wikimedia Commons, 1860)
Notice iconographique issue de Wikimedia Commons. Titre: Siege of Caudebec in 1592 (engraving). Siege of Caudebec in 1592 (engraving)
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie